PENGEMBANGAN BAHAN AJAR EVALUASI PEMBELAJARAN SD UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS MAHASISWA - Theresia Monika Siahaan; Melvin V.M. Simanjuntak (MES: Journal of Mathematics Education and Science, 2026)
This study aims to develop teaching materials for the ‘Primary School Learning Evaluation’ course that can enhance the critical thinking skills of student teachers. The research method employed was Research and Development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects were students on the primary school teacher education programme at HKBP Nommensen University, Pematangsiantar. The research instruments included an expert validation questionnaire, a critical thinking skills test, and a student response questionnaire. The research results indicate that the developed teaching materials meet validity criteria with an average score from validators of 88% (very good category), are practical with high readability and a positive student response rate of 91%, and are effective as demonstrated by an increase in students’ critical thinking skills scores with an average gain score of 0.65 (moderate to high category). Thus, the teaching materials for Primary School Learning Evaluation developed have been proven to be suitable for use and contribute to improving the critical thinking skills of student teachers.